2004
DOI: 10.1021/jf040010+
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Iron Availability from Iron-Fortified Whole-Grain Wheat Flour

Abstract: Iron deficiency is the most common nutritional disorder worldwide. Iron fortification of foods is considered to be the most cost-effective long-term approach to reduce iron deficiency. However, for fortified foods to be effective in reducing iron deficiency, the added iron must be sufficiently bioavailable. In this study, fortification of whole-grain wheat flour with different sources of iron was evaluated in vitro by measuring the amount of dialyzable iron after simulated gastrointestinal digestion of flour b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 19 publications
2
15
0
1
Order By: Relevance
“…Kloots et al (2004) found that the iron dialyzability was higher in chapatis (a typical Indian bread) prepared from whole-grain wheat flour fortified with NaFeEDTA or SunActive® Fe (ferric pyrophosphate) than those fortified with ferrous sulfate. Iron dialyzability from whole-grain wheat flour baked into chapatis was similar for all added iron sources (ferrous sulfate, ferrous lactate, ferrous fumarate, ferric pyrophosphate, carbonyl iron, electrolytic iron, Ferrochel® amino acid chelate, ferric amino acid chelate taste free [TF], and Lipofer™ which is a complex of ferric pyrophosphate, starch, and lecithin).…”
Section: Applications Of In Vitro Methods and Recommendationsmentioning
confidence: 99%
“…Kloots et al (2004) found that the iron dialyzability was higher in chapatis (a typical Indian bread) prepared from whole-grain wheat flour fortified with NaFeEDTA or SunActive® Fe (ferric pyrophosphate) than those fortified with ferrous sulfate. Iron dialyzability from whole-grain wheat flour baked into chapatis was similar for all added iron sources (ferrous sulfate, ferrous lactate, ferrous fumarate, ferric pyrophosphate, carbonyl iron, electrolytic iron, Ferrochel® amino acid chelate, ferric amino acid chelate taste free [TF], and Lipofer™ which is a complex of ferric pyrophosphate, starch, and lecithin).…”
Section: Applications Of In Vitro Methods and Recommendationsmentioning
confidence: 99%
“…For example, water-soluble ferrous sulfate has a good bioavailability, but induces unacceptable color or flavor changes in food (Hurrell, 1997). In contrast, ferric pyrophosphate (FePP) does not induce serious organoleptic change, although it has low bioavailability coming from poor water solubility (Kloots et al, 2004). In case of Zn fortification, zinc sulfate, zinc oxide (ZnO), zinc acetate, and zinc gluconate have been frequently used (Brown and Wuehler, 2000; Brown et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This dialyzability method has been employed as a means for the prediction of iron bioavailability by many researchers (Chiplonkar et al 1999;Drago and Valencia 2004;Hazell and Johnson 1987;Kapsokefalou et al 2005;Kloots et al 2004;). The index employed for the prediction of iron bioavailability is dialyzable iron.…”
Section: In Vitro Methodology For the Prediction Of Iron Bioavailabilitymentioning
confidence: 99%